1993
DOI: 10.1177/000348949310201112
|View full text |Cite
|
Sign up to set email alerts
|

Localized Amyloidosis of the Larynx: Evidence for Light Chain Composition

Abstract: We report the biochemical characterization of amyloid fibrils from a patient with localized amyloidosis of the epiglottis and larynx. Biopsy specimens showed amorphous material consistent with amyloid deposits with a plasmacytic infiltrate. Both plasma cells and amyloid deposits stained positively by immunohistochemistry for kappa light chains. Amyloid fibrils were isolated. The major constituent resolved as a 13 kd band was sequenced and found to be consistent with a kappa 1 light chain. A tryptic digest was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The otherwise benign polyclonal plasma cells produce monoclonal immunoglobulin light chains (L) that are deposited as AL amyloid [ 45 ]. It is still possible that the deposition of amyloid results from the inability of the body to clear light chains produced by plasma cells [ 46 ]. Amyloid deposits in the intestine are usually irreversible but can sometimes be reversible with chemotherapy treatment, especially with melphalan and steroid therapy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The otherwise benign polyclonal plasma cells produce monoclonal immunoglobulin light chains (L) that are deposited as AL amyloid [ 45 ]. It is still possible that the deposition of amyloid results from the inability of the body to clear light chains produced by plasma cells [ 46 ]. Amyloid deposits in the intestine are usually irreversible but can sometimes be reversible with chemotherapy treatment, especially with melphalan and steroid therapy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Although there is no proven link to smoking, vocal misuse, or recurrent infections, 1,9 one theory suggests a response of circulating precursor proteins, plasma cells, and/or immunoglobulins, to localized injury and inflammation. Another more likely theory suggests a localized collection of monoclonal plasma cells 10,11 and inability of the body to clear the excessive or misfolded immunoglobulins produced by monoclonal plasma cells found in the mucosa (mucosa-associated lymphoid tissue or MALT). Westermark hypothesizes further that giant cells, prevalent in localized amyloid deposits but not systemic, are important in transforming the immunoglobulin light chain into the misfolded amyloid fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Antiserum to K or L light-chain protins may be used but this is not as reliable as anti-AA staining (1). Amino acid sequence studies of laryngeal amyloid have shown that the amyloid fibrils are derived from amyloid immunoglobulin light chain (6,7). In this case report, amyloidosis was confirmed by the Congo red staining of the biopsy specimen.…”
Section: Discussionmentioning
confidence: 84%